ANALISA PENERAFANSUBSIDI DANA SUMBANGAN PENDIDIKAN (DSP) DISEKOLAH DASAR, MENENGAH DAN KEJURUAN KOTA CILEGON - Cepi Safruddin Abd. Jabar (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2010)
Educational subsidy program (DSP subsidized) is a supporting program for achieving K-12 compulsory education program in Kota Cilegon. Through the program, Local governments try to eliminate/reduce citizen's expenditures for education phase by phase. This program (DSP subsidized) is aimed to subsidy admission program in first year's school. The purposes of research as such: First, try to describe the adequacy of the program in helping schools achieve their effectiveness. Second, describe how schools utilized the DSP program for finance school activities. This work is using descriptive framework as a guideline. The research was involving 32 SDs (elementary schools), 10 SMPs (Junior High schools), 5 SMAs (High schools), and 2 SMKs (Vocational High schools) as a research samples. Data gathering was using questionnaires and documentation study. The finding shows that (23.8%) schools declare that adequacy of DSP program could meet 8O%-90% school teaching and learning activity needs. For quality improvement, 23.8% schools explain that program could meet 100% needs. For procurements and maintenance, 38.1% school said that the program could meet 40%-70% school needs. Majority schools said that the program could meet 40%-70% school needs for student affairs. 47.6% schools said that the program could meet less than just 40% school prosperity. For supporting school governance, 26.3% school said that the program could meet less than 40% school needs. Keywords: DSP Subsidized, Adequacy, Effectiveness, Efficiencies